Petroleum potential of the Neocomian deposit of Nyurolsky megadepression; IOP Conference Series: Earth and Environmental Science; Vol. 21: XVIII International Scientific Symposium in Honour of Academician M. A. Usov: Problems of Geology and Subsurface Development, 7–11 April 2014, Tomsk, Russia - Osipova E. N. Elizaveta Nikolaevna (Petroleum Geology, 2014)
Title screen